LONGITUDINAL COMPRESSION THERAPY FOR SMALL BOWEL STRICTURE CROHN'S DISEASE: DURABLE RESOLUTION IN SWINE MODEL. (26th January 2023) - Verde, Juan; Chen, Caressa; Brahmstedt, Colin; Lukas, Martin; Kolar, Martin; Laser, Daniel; Salky, Barry; Harrison, Michael; Swanstrom, Lee
Abstract: INTRODUCTION: Small bowel stricture is common in Crohn's disease (CD), both de novo and after resection. With all standard treatments having high recurrence rates, CD patients would benefit greatly from a novel and highly durable non-surgical intervention. We report the first long-term study of longitudinal compression therapy (LCT) for the treatment of anastomotic strictures in an animal CD stricture model. LCT entails progressive endoluminal compression of stricture tissue between two flange-like device components. The goal is to gradually bring about necrosis of fibrotic tissue interposed between the two flanges while allowing remodeling with minimal iatrogenic inflammation around the periphery. METHODS: Stable anastomotic strictures with hallmarks of CD small bowel strictures were created in 6 pigs, using an established method entailing ileocolonic anastomosis creation with a bypassed ileal segment to maintain patency of the gastrointestinal tract followed by serial injections of phenol/trinitrobenzenesulfonic acid at the anastomosis site. Instead of using LCT devices deployed wholly endoscopically, to best study stricture response to LCT in this model, we used devices with magnetic elements for compressive force generation and integrated ultraminiature sensor arrays for monitoring treatment progression; one 23 mm diameter device component was placed via a surgical enterotomy and a second was deployed endoscopically. Animals were followed for 9 weeks after LCT to gauge post-treatment stricture response. RESULTS: LCT device placement was successful in all animals. Five animals reached the 9-week timepoint. One animal was sacrificed on day 12 due to urinary tract complications unrelated to the device. The initial therapeutic response took place over a 3-hour period after device placement, with LCT devices applying increasing force from 3 to 10 Newtons. In endoscopic assessments, widened lumens were noted, with openings 3.3-fold larger at 2 weeks and 3.7-fold larger at 9 weeks. In comparison, for endoscopic balloon dilation in the same animal stricture model, the openings were 2.3-fold larger at 2 weeks, declining to 1.9-fold at 9 weeks. Endoscopic and macroscopic evaluation after euthanasia demonstrated newly patent lumens after excision of stricture tissue, with healthy-appearing mucosa and no macroscopic findings of stricture. CONCLUSION: Prior work by our group and others–in animal models and in a small number of treated patients–has provided favorable indications of efficacy of LCT for treating refractory strictures. To the best of our knowledge, this is the first study to include long-term follow-up of LCT in a validated animal model of Crohn's stricture. This work provides strong preliminary support that LCT's combination of resection and neo-epithelialization can durably resolve CD stricture. LCT clinical studies are planned as a next step. Design and operation of device systems for longitudinal compression therapy for small bowel stricture in Crohn's. (a) Longitudinal compression therapy device systems incorporate a dual-flange design, with a mechanism for drawing the flanges together to longitudinally compress the stricture. For single-sided access, expanding flange designs can be used (inset, top left). The LCT device systems used in this study are pairs of discrete non-expanding flange components, with one flange component placed proximal to the strictured region via laparotomy; magnetic elements in the flange components supply the compressive force. This design facilitates incorporation of ultraminiature sensor arrays into the flange components for monitoring stricture response to treatment (inset bottom right). (b)-(d) Steps in longitudinal compressive therapy: (b) advancing the LCT device through the stricture; (c) stricture compression between distal flange and expanded proximal flanges; (d) completion of therapy. Representative result for LCT in the porcine model of Crohn's small bowel stricture. (a) Before treatment, a length of bowel 15 mm long is badly strictured, with the lumen less than 10 mm at its narrowest point. (b) At 2 weeks after LCT treatment, the narrowest point is markedly larger. (c) At 9 weeks post LCT treatment—a time after which balloon dilated strictures tend to have recurred—the LCT treated stricture is even more open than at 2 weeks post, consistent with the LCT intervention having spurred healing instead of exacerbating fibrosis. Three-dimensional anatomy of strictured segments determined by impedance-based measurement (Endoflip, Medtronic).